Medieval lime-gypsum mortars in Ireland - Pavia, Sara (My University, 2023)
Historic lime-gypsum mortars are rare in Ireland. Gypsum is hygroscopic and relatively soluble in water, hence common believe was that it would hydrate in the highly- humid Irish climate to quickly weather. The material sources and fabrication technology of original mortars in the Kells Round Tower, built c.9th-10th centuries are studied. The results evidenced that hydraulic, gypsum-lime mortars were used to build the tower. Their binder is a mixture of lime and gypsum. Rather than mixing lime with gypsum, the binder was made by burning a carbonate-gypsum rock (probably a marl) at the high temperatures typical of traditional gypsum production (~800°C). The mortars are hydraulic, as indicated by the high- temperature transformations evidenced with petrography, whereby clay minerals and carbonate have turned into calcium silicates. The presence of calcium silicates (in aggregates and lime inclusions) indicate that the mortars are hydraulic, and that a carbonate-gypsum rock was burned over 800°C to produce the binder. The mortars were made with local materials. The use of gypsum this early is surprising. However, there are gypsum mines near Kells, at a short distance that could have been easily sorted in historic times. The parent rock used to make the binder was probably a marl, quarried in the Carrickmacross-Kingscourt area, c.10 km North of Kells. Despite the gypsum content, the mortars have endured the Irish climate for about 1,000 years because the composition of the parent rock and the high production temperature afforded hydraulic properties to the mortars, and hence an enhanced durability. No other instances of use of gypsum-lime mortars in medieval times in Ireland have been reported to date.
C O N F. I N T. S U R L A C H A U X (CIC-2023)
Keywords: Lime-gypsum mortar; Calcium silicates; Hydraulic gypsum mortars; Historic mortars; Nanoscience & Materials